ANALISIS KOMPETENSI PELATIHAN DAN PENGAWASAN TERHADAP KINERJA KARYAWAN PT. TOYOTA ASTRA MOTOR - Endah Pujiastuti (POLITEKNIK LP3I JAKARTA, 2025)
Examining the interconnected dynamics of competence, training, and supervision as well as their individual and combined effects on worker performance is the goal of this study. Through the use of quantitative research methods, this study collects data mostly through interviews using a quantitative descriptive framework. The partial analysis's findings show that PT. Toyota Astra Motor employees' performance is positively impacted by competence in a statistically meaningful way. The results also show that employee performance inside the company is positively and significantly impacted by training. Additionally, it was discovered that PT. Toyota Astra Motor employees' performance was positively and significantly impacted by supervision. The simultaneous analysis's findings highlight how competence, training, and supervision all work together to significantly and favorably impact employee performance inside the same company. Training and communication account for 93.7% of the variance in employee performance, according to the adjusted R2 value, meaning that other independent variables not included in this study may be responsible for the remaining 6.3%.